1990
DOI: 10.1136/bjsm.24.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of taping for the prevention of ankle ligament sprains.

Abstract: The effectiveness of taping in the prevention of sports injuries has only been studied in detail with regard to the lateral ligaments of the ankle. It appears that taping can protect against injury. The mechanism by which taping works is not certain, but mechanical factors play a role which decreases with exercise. The major effect of taping may be its proprioceptive effect on underlying muscle groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…This biomechanical adaptation hypothetically can increase the period of time before dangerous loading of the joint and can thus provide sufficient time for joint protective mechanisms (proprioceptive information and muscle response) to act for elimination or reduction of the injury risk. Such protective biomechanical adaptations have been clearly reported in ankle-and shoulder-taping studies 8,[47][48][49] and, in theory, can be attributed to a lesser extent to ENAB.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This biomechanical adaptation hypothetically can increase the period of time before dangerous loading of the joint and can thus provide sufficient time for joint protective mechanisms (proprioceptive information and muscle response) to act for elimination or reduction of the injury risk. Such protective biomechanical adaptations have been clearly reported in ankle-and shoulder-taping studies 8,[47][48][49] and, in theory, can be attributed to a lesser extent to ENAB.…”
Section: Discussionmentioning
confidence: 82%
“…Several other studies have shown that anelastic taping of a joint or the application of an Aircast orthosis will lead to a significant reduction in both passive and active ankle ROM. 8,[50][51][52] Literature regarding enhancement of sports-injuryrehabilitation processes through ENAB has been limited to the comparison between ENAB and semirigid ankle supports. 18,[26][27][28] Evidence to date suggests that rehabilitation with the use of ENAB may be useful in terms of edema reduction and controlled ROM in non-weight bearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect, in combination with recommendations of braces for individual requirements, was addressed in a recent study by Eils et al 7 Regarding the effect of taping on the incidence of ankle sprains, it was shown that the use of tape led to a significant decrease of ankle injuries, whereas tape seemed to be less effective as compared to braces. 11,13,20,26 In addition, it was shown that the mechanical stability of tape was nearly completely lost after 20 minutes of exercise. 34 Therefore, the preventive effect of tape must have a different cause than sole mechanical stability.…”
Section: External Stabilizing Devicesmentioning
confidence: 99%
“…These external supports are thought to have both mechanical and neuromuscular effects that aid in injury prevention. 11,14,55 Taping and bracing have been shown to be effective at reducing the risk of ankle sprains, especially among those with a prior history of ankle sprains. 41 There are some limitations of the research of these techniques.…”
Section: Clinical Practice Techniquesmentioning
confidence: 99%